Exploratory Structural Equation Modeling Analysis and Validity of the Family Needs Screener - Kaye, Miranda P. (Journal of interpersonal violence, 2021)
Assessment that accurately categorizes families’ risk for family violence (i.e., intimate partner violence and child maltreatment) and identifies areas of family need is essential for prevention program planning, practice, and resource allocation. The Family Needs Screener (FNS) assesses risk for intimate partner violence and child maltreatment. It is used as a tool to prioritize those who are in the greatest need of services as well as plan prevention efforts in selected prevention services offered to military families. To date, no peer-reviewed studies examine the factor structure of the FNS. In this study, we examined measurement aspects of the FNS as an assessment tool in identifying risk of family violence. Data were drawn from Army families (N = 18,159) who were screened between 2009 and 2013 and matched to substantiated cases of family violence. Exploratory structural equation modeling (ESEM) was used to examine the factor structure, measurement invariance, and predictive validity of the FNS. Results supported a shortened measure with a five-factor structure and full gender invariance. In particular, relationship issues were predictive of both intimate partner violence and child maltreatment. In addition, family of origin/history of family violence was predictive of substantiated cases of child maltreatment. Findings support the use of the FNS to assess risk, allocate, and plan for services in an Army population. Implications for scale modifications and use, as well as prevention efforts, are discussed.